2015
DOI: 10.4103/0973-1482.150345
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis as a prognostic factor in patients with renal cell carcinoma: A meta-analysis of literature

Abstract: Thrombocytosis indicates worse OS and CSS for patients with RCC, and it showed stronger specificity or sensitivity for CSS. Thrombocytosis is more frequently in patients with metastatic RCC but only showed significant influence on survival of localized RCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Growing evidence has reported that platelets can prevent death of cancer cells by natural killer cells, and can secrete angiogenic and tumor growth factors to promote cancer growth, progression and metastasis [ 35 37 ]. Furthermore, it has been reported that thrombocytosis is associated with poor prognosis in renal cancer [ 38 , 39 ]. While lymphocytes are the main components of immune system in the host and can destroy tumor cells and prevent cancer progression [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has reported that platelets can prevent death of cancer cells by natural killer cells, and can secrete angiogenic and tumor growth factors to promote cancer growth, progression and metastasis [ 35 37 ]. Furthermore, it has been reported that thrombocytosis is associated with poor prognosis in renal cancer [ 38 , 39 ]. While lymphocytes are the main components of immune system in the host and can destroy tumor cells and prevent cancer progression [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…More and more evidences have recognized that hemostatic variables, particularly platelet counts and plasma fibrinogen levels, have prognostic significance in patients with cancer [1013, 17]. Platelets and fibrinogen together actively plays an important role in tumor growth, invasion and hematogenous metastasis by promoting tumour neovascularization and by supporting the sustained adhesion of tumour cells [8, 1819].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed an important link between hemostatic factors and innate immunity and indicate that one mechanism by which the platelet-fibrin(ogen) axis contributes to metastatic potential is by impeding natural killer cell elimination of tumor cells [7]. In various types of cancer, thrombocytosis and PLR were proved to have a close relationship with survival outcomes [1011, 17]. Recently, a meta-analysis of 12 studies including 8735 renal cell carcinoma patients showed thrombocytosis had a significant influence of 5-year OS and CSS in patients with localized renal cell carcinoma [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombocytosis has been identified as an adverse prognostic indicator in lung cancer [ 7 ], esophageal cancer [ 8 ], renal cell carcinoma [ 9 ], and gynecological malignancies [ 10 11 ], and breast cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%